2003
DOI: 10.1128/jvi.77.19.10575-10583.2003
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Nucleic Acid Packaging Signals To Generate a Novel Influenza Virus-Based Vector Stably Expressing Two Foreign Genes

Abstract: At the final step in viral replication, the viral genome must be incorporated into progeny virions, yet the genomic regions required for this process are largely unknown in RNA viruses, including influenza virus. Recently, it was reported that both ends of the neuraminidase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
175
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(182 citation statements)
references
References 43 publications
4
175
2
1
Order By: Relevance
“…Similar studies have now been reported for all eight segments (summarized in Fig. 4c), and in every case, the terminal coding regions, comprising sequences unique for each segment, have been found to promote more efficient packaging than the UTRs alone (Dos Santos Afonso et al, 2005;Fujii et al, 2003;Fujii et al, 2005;Gog et al, 2007;Liang et al, 2005Liang et al, , 2008Marsh et al, 2007;Muramoto et al, 2006;Ozawa et al, 2007Ozawa et al, , 2009Watanabe et al, 2003). The observation that virus formation is inefficient in the absence of the terminal regions of all eight vRNAs has also been corroborated and extended by examining the effects of removing other segments (de Wit et al, 2006;Fujii et al, 2009;Gao et al, 2008;Gao & Palese, 2009;Marsh et al, 2007).…”
Section: Genome Segmentation: a Mixed Blessingmentioning
confidence: 50%
See 2 more Smart Citations
“…Similar studies have now been reported for all eight segments (summarized in Fig. 4c), and in every case, the terminal coding regions, comprising sequences unique for each segment, have been found to promote more efficient packaging than the UTRs alone (Dos Santos Afonso et al, 2005;Fujii et al, 2003;Fujii et al, 2005;Gog et al, 2007;Liang et al, 2005Liang et al, , 2008Marsh et al, 2007;Muramoto et al, 2006;Ozawa et al, 2007Ozawa et al, , 2009Watanabe et al, 2003). The observation that virus formation is inefficient in the absence of the terminal regions of all eight vRNAs has also been corroborated and extended by examining the effects of removing other segments (de Wit et al, 2006;Fujii et al, 2009;Gao et al, 2008;Gao & Palese, 2009;Marsh et al, 2007).…”
Section: Genome Segmentation: a Mixed Blessingmentioning
confidence: 50%
“…Also, depending on the experimental design, the reporter construct may or may not be competing for packaging with the genomic segment from which it was derived, while requirements for packaging may differ for single-cycle and multi-cycle growth. Watanabe et al, 2003). In all cases, segments were found to have a bipartite specific packaging signal that involved extended sequences at both ends of the vRNA (Fig.…”
Section: Defining Segment-specific Packaging Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that soon after budding, the influenza A virus ribonucleoprotein (RNP) complexes inside the virions form a specific architecture: a central segment surrounded by the seven other vRNPs (2), which suggests that influenza viral RNA (vRNA) packaging is not a random process. Moreover, segment-specific RNA packaging sequences have been identified on each segment of the influenza A/WSN/33 virus (3)(4)(5)(6)(7)(8)(9)(10)(11). A common feature of these packaging signals is that both the 3Ј and 5Ј noncoding regions (NCRs), as well as coding sequences at the two ends of each open reading frame (ORF) are important [(3-11) and Fig.…”
Section: Nfluenza Viruses Are Classified As Members Of the Familymentioning
confidence: 99%
“…Amino acid at position 473 (in the peptide of 473-481) in the nucleoprotein was relatively conserved in subtype H1N1 and H3N2 IAVs, and was reported to stimulate the host to produce IFN-c (Wahl et al, 2009). These findings are of interest because the non-coding regions and some coding regions of genome segments affect viral RNA synthesis and packing (Liang et al, 2005;Muster et al, 1991;Ng et al, 2008;Sun et al, 2015;Watanabe et al, 2003;Zheng et al, 1996). Further experiments are needed to validate the roles of sequence changes in the discrepancy seen in patterns of virus shedding and antibody response dynamics between the swine in the treatment and sentinel groups.…”
Section: Evaluation Of Current Protocols For Using An Ai Multis-screementioning
confidence: 82%